SELEKTIF DALAM MEMILIH PRODUK KONSUMSI KELUARGA DALAM MENINGKATKAN KETAHANAN PANGAN SELAMA PANDEMI COVID-19 - Sandya, Ezra Chica'al; Munif, Ngabdul (Prosiding Pendidikan Teknik Boga Busana, 2021)
Background: The Covid-19 pandemic is currently attracting public attention. It appears that the health and wellbeing behaviors of both health behavior, dietary habits, and food security are evident. Purpose: This study aims to look at a picture of people's lives, especially in being selective in choosing family consumption products for food security during the Covid-19 pandemic. Methodology: Data collection is done by filling out a questionnaire that was previously created and entered in the Google Form application with 80 respondents. Results: Based on data analysis, the most information obtained about Covid-19 was obtained from thesocial media as much as 56%. The motivation of consumers in buying products is 72.40% because it is to fulfill their needs. 41.3% of places to shop during Covid-19 at the nearest store. Information about buying necessities obtained from individuals (family, neighbors, and acquaintances) was 55.5%. Eating habits, diversity of food methods of obtaining, processed food that learned, and bought food obtained an average of 73.9%. Conclusion: Being selective in choosing family consumption products both from increasing eating habits also affects the diversity of food eaten, as well as experiencing an increase in the frequency and number of meals. Keywords: selective, consumption, food security, Covid-19